A proposed mechanism to improve science instruction - Versales, Miraflor B (UPV-Cebu College, 2001)
This study was conducted in St. Scholastica's Academy, Tabunok, Talisay City, Cebu during the SY 1999-2000. Baseline data were gathered concerning science teachers' educational background; teaching styles; the correlation of year level, gender, socio-economic status to learning style; and students' preferences for learning activities, groups and resources. Descriptive-Correlation was employed in this study. Percentages and Weighted Mean were used to describe most of the data. ANOVA was also used to determine significant differences while Logistic Regression was used to determine correlation. The findings revealed that the science teacher of St. Scholastica's Academy were prepared to tech their respective subjects and had a predisposition towards the field independent teaching style. They used the Listening-Speaking Method most of the time. The whole class was also often used as a learning group with books constantly used as a learning resource. The students o the other hand, had inclinations toward the field dependent learning style. It was also observed that learning style of the respondents depended on year level and gender but did nt depend on socio-economic status. Students' preferences were for the Watching-Doing Methods. Field trip, Games and hands-on Laboratory were chosen highly. Students also opted for Groups instead of the other learning groups. For learning resources, books and television were the choices of the students. From these findings, guidelines were formulated. The guidelines stressed the necessity to identify the teachers' teaching styles and students' learning styles. The science teachers should also provide variety of classroom activities to satisfy the learning needs of students. The researcher also recommended that science teachers be given training on the use of different teaching strategies preferably on student-centered approaches. Science teachers should also be trained on the preparation of instructional devices and the use of updated learning resources.